2014
DOI: 10.1002/jat.3057
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of cytosolic calcium by 2‐aminoethoxydiphenyl borate and caffeine affects zebrafish myofibril alignment

Abstract: The objective of the current study was to investigate the effects of Ca(2+) levels on myofibril alignment during zebrafish embryogenesis. To investigate how altered cytoplasmic Ca(2+) levels affect myofibril alignment, we exposed zebrafish embryos to 2-aminothoxyldiphenyl borate (2-APB; an inositol 1,4,5-trisphosphate receptor inhibitor that reduces cytosolic Ca(2+) levels) and caffeine (a ryanodine receptor activator that enhances cytosolic Ca(2+) levels). The results demonstrated that the most evident change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Exposure of zebrafish embryos to 2‐aminothoxyldiphenyl borate (2‐APB), a chemical can reduce cytosolic Ca 2+ levels, led to split and short myofibril phenotypes. On the contrary, embryos treated with caffeine, a reagent can enhance cytosolic Ca 2+ level, displayed twisted and wavy myofibril morphology . Our data indicated that 4‐MI‐treated zebrafish embryos exhibited wavy and misaligned myofibrils which are highly similar to those of zebrafish embryos with calcium imbalance.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Exposure of zebrafish embryos to 2‐aminothoxyldiphenyl borate (2‐APB), a chemical can reduce cytosolic Ca 2+ levels, led to split and short myofibril phenotypes. On the contrary, embryos treated with caffeine, a reagent can enhance cytosolic Ca 2+ level, displayed twisted and wavy myofibril morphology . Our data indicated that 4‐MI‐treated zebrafish embryos exhibited wavy and misaligned myofibrils which are highly similar to those of zebrafish embryos with calcium imbalance.…”
Section: Discussionmentioning
confidence: 60%
“…During zebrafish myogenesis, myofibril alignment is regulated by several factors, including calcium concentration, nerve activity and MRFs. Previous reports demonstrated that proper cytosolic calcium concentration can regulate myod expression and myofibrils alignment . Exposure of zebrafish embryos to 2‐aminothoxyldiphenyl borate (2‐APB), a chemical can reduce cytosolic Ca 2+ levels, led to split and short myofibril phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A green fluorescent vascular endothelium transgenic line was used to assess the induced toxicity of caffeine during embryonic vascular development, but no defects were found in vasculogenesis; however, real-time PCR showed that caffeine treatment can disturb the angiogenesis of zebrafish embryos (Yeh et al, 2012). Interestingly, Wu et al (2015) exposed zebrafish embryos to both 2-APB and caffeine and found no malformed phenotypes, which was totally different from the results found with the phenotype treated with 2-APB alone. Increasing exposure time to caffeine may have triggered apoptosis, but neither significant mortality nor morphological changes could be detected.…”
Section: Common Nutraceuticals Assessment With Zebrafishmentioning
confidence: 77%